A numerical interfacial approach to investigate the melting heat diffusion in the conical flow of hydrodynamic Casson Ferro liquid. (9th December 2022) - Minnam Reddy, Vasudeva Reddy; R., Suresh Babu; B. K., Naveen Kumar; Sandeep, N.
Abstract: The conical flow has its significance in the thermal design of high-speed missiles and shock jump conditions. Buoyancy-driven melting heat transfer in hydrodynamic Casson ferroliquid flow over a conical surface is assessed numerically. The buoyancy force, uneven heat sink/source, radiative heat, melting heat, and Ohmic heat are considered physical relevance. The water-based cylindrical-shaped cobalt (Co) nanoparticles are measured. The thermal conductivity of ferrofluid is measured by assessing the Hamilton-Crosser, and interfacial layer approaches. A mathematical model was established and resolved computationally using the Lobatto-IIIA-based Matlab scheme. Simultaneous results are explored and explained with the help of pictorial and mathematical outcomes. The Hamilton-Crosser model reported a higher thermal conductivity than the interfacial layer approach for Casson ferrofluid flow.